Andrographolide prevents acute hyperammonemia-induced motor dysfunction in rats. Evidences for its mechanism of action - Arghya Mukherjee; Santosh Singh (Phytomedicine Plus, 2025)
Background: Beside the cirrhotic one, non-cirrhotic hyperammonemia (HA) can also cause neuro-degeneration and establishment of 'Hyperammonemic Encephalopathy', ultimately leading to the coma stage. We have done pilot study on aqueous extract of Andrographis paniculata herb against HA induced oxidative stress in rats. Andrographolide (AGP) is the major component isolated from of A paniculata and reported to have various biological activities. Purpose: Present study aimed to explore the therapeutic potentiality of AGP on rat model of non cirrhotic acute HA. Methods: Rotarod and traction test was performed to access the motor function. Brain and serum ammonia level were assayed to confirm occurrence of HA. Malondialdehyde (MDA), reduced glutathione (GSH), protein carbonylation levels and activity of superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx), glutathione reductase (GR) were studied as oxidative stress markers. Expression of two NMDAR subunits, NR2A, 2B, nNOS and level of nitrite (NO2), cGMP in cerebral cortex and cerebellum were assayed to study the NMDAR-nNOS-cGMP cascade. Result: Acute HA caused motor dysfunction in rats. MDA level and protein carbonylation, increased significantly while SOD, catalase, GPx and GR got suppressed and NMDAR-nNOS-cGMP cascade activated in cerebral cortex and cerebellum. All these suggested establishment of hyperammonemic encephalopathy. AGP treatment restored the motor function, lowered the ammonia level, suppressed the oxidative stress markers, NR2A, 2B, nNOS over-expression and elevated NO2, cGMP levels in cortex and cerebellum. Conclusion: Our study showed AGP could be a potential natural anti-hyperammonemic drug as it has prevented the development of acute hyperammonemic encaphalopathy in rats by suppressing NMDAR-nNOS-cGMP cascade and oxidative stress in cerebral cortex and cerebellum.